Breaking borders: navigating gender norms and realities in Ali’s Brick Lane and Desai’s fasting feasting - Khan, Fariha Ahmed (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2024.